PHYSICO-CHEMICAL CHARACTERIZATION OF WATER WELLS FROM REMETI, MARAMURES - DIPPONG, Thomas; KOVACS, Eniko; COMAN, George; BUD, Sebastian; ȚÎBÎRNAC, Marcel; PAYER, Maria Magdalena; MARIAN, Monica; MARE ROSCA, Oana; MIHALI, Cristina; HOAGHIA, Maria-Alexandra (Studia Universitatis Babeș-Bolyai Chemia, 2021)
This study was conducted with the aim of determining the quality and potential contamination level of water wells. Samples were collected from private water wells used as drinking water sources in Remeți locality, Maramures County, Romania. Remeți is situated near the protected area of the Upper Tisa River. Several physico-chemical indicators were determined, such as pH, electrical conductivity, dissolved oxygen, oxygen saturation, turbidity, temperature, ammonium, nitrate, nitrite, chloride, phosphate, iron, copper, sulphates, carbonate, bicarbonate and total hardness, due to their importance to human health and to the quality of the aquatic systems situated nearby a protected area. The quality status was assessed by using the water quality index (WQI), based on eleven parameters: pH, electrical conductivity, ammonium, total hardness, turbidity, nitrite, nitrate, chloride, sulphate, iron and cooper. The results indicated high amounts of ammonium and nitrate, while the WQI classified the studied water well samples into excellent and good quality categories. The WQI scores ranged between 27.7 and 65.1. The novelty of the study consists in the determination of the chemical composition of water wells from Remeti locality and in identification of some pollution processes which could affect human health if the studied waters are used as drinking water sources.